Optimization of chemical conditions for metabolites production by Ganoderma lucidum using response surface methodology and investigation of antimicrobial as well as anticancer activities - Tajik, Alireza; Samadlouie, Hamid Reza; Salek Farrokhi, Amir; Ghasemi, Amir (Frontiers in Microbiology, 2024)
Ganoderma lucidum (G. lucidum) is a medical mushroom known for its tendency to produce physiologically active constituents with far-reaching effects on human health. Herein, the significance of titanium dioxide (TiO2 NPs), magnesium oxide nanoparticles (MgO2 NPs) and vitamin B6 along with various microelements were examined in the rise of polysaccharide and ganoderic acid (GA) via One Factor At time. TiO2 NPs, MgO2 NPs and B6 along with glucose syrup and CLS syrups were discovered to be best for GA productions. Wheat starch and whey protein along with MgO2 NPs and B6 vitamin stimulated polysaccharide production. After screening, response surface method (RSM) statistically predicted that the media containing (g/l): 42.11 wheat starch with 22 whey protein and 50 glucose syrups with 30 CSL were the optimal chemical conditions for polysaccharide (21.47 percentage of dry weight biomass (DWB)) and GA (20.35 mg/g DWB) production respectively. The moss of the fruit body of G. lucidum produced under the optimal condition of GA was of the highest variation in flavonoids and phenolic acids with significant antimicrobial activity against Esherichia coli and Bacillus subtilis. Moss, stem and shell of G. lucidum aggravated the substantial MDA-MB-231 cell death in a dose of 500 µg/ml. The IC50 levels of shell and stem of G. lucidum were 465.3 and 485.7 µg/ml, while moss did not reach 50% inhibition.